Type 2 reaction associated sensorineural hearing loss in a drug resistant lepromatous leprosy patient: A case report - Harpreet Singh Pawar; Itu Singh; Harish Kumar Sagar (Asian Pacific Journal of Tropical Medicine, 2023)
Rationale: Leprosy, a chronic granulomatous disease often present clinically as erythema nodosum leprosum, a type 2 reaction. The involvement of cochlear part of audiovestibular system is a rarity. Patient concerns: A 26-year-old male patient with lepromatous leprosy developed bilateral sensorineural hearing loss (SNHL) during type 2 reactional episode. Diagnosis: Recurrent erythema nodosum leprosum in rifampicin-resistant lepromatous leprosy. Interventions: Corticosteroids and second-line multidrug therapy. Outcomes: The patient improved significantly and was further referred for management of psychosocial impact due to sensorineural hearing loss. Lessons: The hearing impairment is a rare complication of type 2 reaction. Any patient with suspected cranial nerve involvement should essentially be screened by tuning fork tests for early detection of hearing impairment and offer timely intervention as required. All high bacteriological index cases should be investigated for antimicrobial resistance in high endemic areas.